Sistem Pengupahan Pekerja Dalam Perspektif Ekonomi Islam (Studi Kasus di CV. Motor Jaya 2 Gending) - M. Khoiruddin; Imam Syafi'i; Ahmad Fajri (DPPM Universitas Pelita Bangsa, 2024)
This research aims to find out in detail about the worker wage system from an Islamic economic perspective applied at CV. Motor Jaya 2 Gending In this research, researchers used field study research. Field research used in qualitative research produces data which is interpreted as facts or information from actors (research subjects, information, actors, activities and places are the research subjects). Meanwhile, this type of research uses a case study type. A case study is part of a qualitative method that seeks to explore a particular case in more depth by involving the collection of various sources of information. The data source was obtained directly from the research location at the CV office. Motor Jaya 2 Gending through documents related to the problems studied. Apart from that, data was also obtained through interviews with the company manager and the Accounting Finance Officer Manager. Once collected completely, it is then analyzed descriptively where specific conclusions are drawn from the general data that has been collected. The results of this research show that in general the wage provisions of CV companies.